2008
DOI: 10.1007/s10750-008-9674-8
|View full text |Cite
|
Sign up to set email alerts
|

An overview of integrated hydro-ecological studies in the MELMARINA Project: monitoring and modelling coastal lagoons—making management tools for aquatic resources in North Africa

Abstract: As landscape disturbance and climate conspire to accelerate global environmental change towards unprecedented levels in the twenty-first century, the populated coastal regions of many countries are facing major threats to sustainability. Coastal water resources are particularly vulnerable in dry regions. In view of the expected severity of future environmental change in the Southern Mediterranean Region, the European Commission supported an integrated multidisciplinary project, MELMARINA, on monitoring and mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…Ambos os trabalhos chineses focavam a gestão integrada na bacia de drenagem (RAVESTEIJN et al, 2009;YANG & GRIFFITHS, 2010). Também foram identificadas duas publicações no continente africano, uma com foco na gestão integrada de bacias hidrográficas, empregada pela DQA e outra discutindo, entre outros fatores, a possibilidade de adequação da DQA no que diz respeito ao alcance do bom estado ecológico (FLOWER & THOMPSON, 2009ae 2009b Pesquisas científicas que levem em consideração tal assunto estão sendo efetuadas. Em Minas Gerais, por exemplo, questões sobre o estabelecimento das condições de referência foram abordadas (MOLLOZI, 2011).…”
Section: A Implementação Da Dqa Em Países Não Pertencentes à Ueunclassified
“…Ambos os trabalhos chineses focavam a gestão integrada na bacia de drenagem (RAVESTEIJN et al, 2009;YANG & GRIFFITHS, 2010). Também foram identificadas duas publicações no continente africano, uma com foco na gestão integrada de bacias hidrográficas, empregada pela DQA e outra discutindo, entre outros fatores, a possibilidade de adequação da DQA no que diz respeito ao alcance do bom estado ecológico (FLOWER & THOMPSON, 2009ae 2009b Pesquisas científicas que levem em consideração tal assunto estão sendo efetuadas. Em Minas Gerais, por exemplo, questões sobre o estabelecimento das condições de referência foram abordadas (MOLLOZI, 2011).…”
Section: A Implementação Da Dqa Em Países Não Pertencentes à Ueunclassified
“…For instance, Reiser et al (1989) showed IFIM to be the most commonly used environment flow management in North America, applied in 38 states or provinces by the late 1980s, and the preferred methodology in 24 cases. Milhous (1998) reported its application in assessment of sediment flushing flows, while Flower and Thompson (2008) provided examples of its application in North African river restoration projects. Furthermore, a total of 616 IFIM applications, specifically by US Fish and Wildlife Service (USFWS) offices, were reported in 1988 (Armour and Taylor, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Lagoon-barrier environments are estimated to occupy 13% of coastal areas worldwide (Duck and De Silva 2012) where they are found along tectonically-stable, low-lying coastlines. They are highly productive ecosystems that provide a wide range of natural functions (Flower and Thompson 2008). The lagoons and the barriers fronting them formed as sea levels rose at the start of the Holocene.…”
Section: Introductionmentioning
confidence: 99%